2002
DOI: 10.1021/jp0210226
|View full text |Cite
|
Sign up to set email alerts
|

On the Electronic Structure of Bis(η5-cyclopentadienyl) Titanium

Abstract: Prior to the first reported synthesis of the titanium analogue of ferrocene, bis(η5-cyclopentadienyl)Ti, there was theoretical speculation as to the electronic structure of what would become known as “titanocene”. In time, the original report of a successful synthesis was apparently shown to be incorrect, and a dimeric form of the substance was postulated as the correct structure. In the present work, high level ab initio and DFT calculations are performed on the titanocene monomer to help answer these structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
(37 reference statements)
3
22
0
Order By: Relevance
“…Photophysical properties were calculated using Time dependent Density Functional Theory (TD-DFT) [35]. The validity of this approach for transition-metal clusters has been checked by several authors [36][37][38]. The functionals employed were the hybrid B3LYP [39][40][41] and the pure mPWPW91, which employs the exchange functional of Perdew and Wang as modified by Barone [42] and the original correlation functional developed by Perdew and Wang [43].…”
Section: Methodsmentioning
confidence: 99%
“…Photophysical properties were calculated using Time dependent Density Functional Theory (TD-DFT) [35]. The validity of this approach for transition-metal clusters has been checked by several authors [36][37][38]. The functionals employed were the hybrid B3LYP [39][40][41] and the pure mPWPW91, which employs the exchange functional of Perdew and Wang as modified by Barone [42] and the original correlation functional developed by Perdew and Wang [43].…”
Section: Methodsmentioning
confidence: 99%
“…Freitag and Gordon [16] calculated using various correlated methods that the triplet ground state ( 3 B 1 ) C 2v titanocene is 21-88 kJ mol À1 (5.0-21.0 kcal mol À1 ) below the lowest energy singlet (C 2v 1 A 1 ). Our value of energy difference between ground state titanocene 1t and lowest energy singlet titanocene 1s obtained at B3LYP/6-311+G(2d,p) level of theory is 33 kJ mol À1 .…”
Section: Calculationsmentioning
confidence: 99%
“…In their quantum chemical survey of the electronic structure of these titanocenes they found that at all levels of theory they used, the triplet geometries were all lower then the lowest energy singlet and that the 3 B 1 (C 2v ) state was a ground state at MP2, B3LYP and CCSD(T) levels of theory. Based on results of their MCSCF calculation, Freitag and Gordon also concluded that a single-reference wave function is appropriate for theoretical treatment of titanocene [16]. Some DFT calculation results concerning titanocene can also be found in papers by Harrod et al [17] and Lee et al [18].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations